Sensus Fidelium and Canon Law: Sense and Sensitivity? - SHCJ, Helen Costigane (New Blackfriars, 2017)
Canon law has had a negative press for many years and is often seen as insensitive, unnecessary or static. This article looks at the origins and sources of the 1983 Code of Canon Law, what it covers, and who is expected to hear it. It considers to what extent canon law finds a resonance in the minds and hearts of the People of God, ways in which the echo is heard or not, and the response of the supreme legislator to this. The idea of 'law in theory' and 'law in action' is explored in relation to a particularly neuralgic issue today, that of governance, and then three issues are considered where there continue to be particular problems of reception.